Functional Proteomic Analysis of Repressive Histone Methyltransferase Complexes Reveals ZNF518B as a G9A Regulator - Maier, Verena K. (Mol Cell Proteomics, 2015)
Cell-type specific gene silencing by histone H3 lysine 27 and lysine 9 methyltransferase complexes PRC2 and G9A-GLP is crucial both during development and to maintain cell identity. Although studying their interaction partners has yielded valuable insight into their functions, how these factors are regulated on a network level remains incompletely understood. Here, we present a new approach that combines quantitative interaction proteomics with global chromatin profiling to functionally characterize repressive chromatin modifying protein complexes in embryonic stem cells. We define binding stoichiometries of 9 new and 12 known interaction partners of PRC2 and 10 known and 29 new interaction partners of G9A-GLP, respectively. We demonstrate that PRC2 and G9A-GLP interact physically and share several interaction partners, including the zinc finger proteins ZNF518A and ZNF518B. Using global chromatin profiling by targeted mass spectrometry, we discover that even sub-stoichiometric binding partners such as ZNF518B can positively regulate global H3K9me2 levels. Biochemical analysis reveals that ZNF518B directly interacts with EZH2 and G9A. Our systematic analysis suggests that ZNF518B may mediate the structural association between PRC2 and G9A-GLP histone methyltransferases and additionally regulates the activity of G9A-GLP.